Roh Kudus dan Good Governance dalam Konteks Gereja Pentakostal-Karismatik - Minggus Minarto Pranoto (STFT Jakarta, Indonesia, 2021)
This article aims to emphasize the importance of the concept of good governance for Pentecostal-Charismatic churches, which are prone to scandals, especially in financial cases. The leadership system centered on one spiritual leader without being critical causes the risk of financial scandals. Methodologically, this essay uses the theories of good governance developed in the context of modern organizations or institutions whose participation, accountability, transparency, and authority values demonstrate good governance to support the primary standards of action and behavior of stakeholders. This article brings into dialogue these theories with the Pentecostal-Charismatic theology that focuses on the work and experience of the Holy Spirit. It further integrates practical and systematic theology. The author argues that the implementation of good governance is critical to regulating the organizational life of Pentecostal-Charismatic churches that emphasize work and experience with the Holy Spirit to manage a healthy and proper church life.